Stability and dye inclusion of graphene oxide/polyelectrolyte layer-by-layer self-assembled films in saline, acidic and basic aqueous solutions - Szabó Tamás; Péter Zsolt; Nyergesné Illés Erzsébet; Janovák László; Talyzin Alexandr (2017)
We demonstrate that a simple spectrophotometric method can be efficiently applied for the characterization of structural and chemical stability and adsorption properties of composite graphene oxide (GO) films in various solutions. The immersion stability of GO layer-by-layer (LbL) self-assembled with a polycation into ultrathin multilayered films was studied in water and in concentrated salty, acidic and basic solutions by UV–visible spectroscopy. These films were found to retain both their chemical stability and physical integrity in water, salt and HCl solutions with a slight rearrangement of the nanoscale structure as shown by the change in their visible spectrum. However, immersion into NaOH solutions above molar concentration led to the deconstruction of the multilayer structure by base-induced deoxygenation of GO. The adsorption of methylene blue on polymer/GO LbL films of various thicknesses revealed that the multilayers are largely impermeable towards this cationic dye. © 2016 Elsevier Ltd